A Systematic Review and Meta-Analysis of the Global Burden of Chronic Pain Without Clear Etiology in Low- and Middle-Income Countries: Trends in Heterogeneous Data and a Proposal for New Assessment Methods. (September 2016) - Jackson, Tracy; Thomas, Sarah; Stabile, Victoria; Shotwell, Matthew; Han, Xue; McQueen, Kelly
Abstract : BACKGROUND: The global burden of chronic pain is projected to be large and growing, in concert with the burden of noncommunicable diseases. This is the first systematic review and meta-analysis of the prevalence of chronic pain without clear etiology in general, elderly, and working populations of low- and middle-income countries (LMICs). METHODS: We collected and reported data using Preferred Reporting Items for Systematic Review and Meta-Analysis (PRISMA) guidelines, excluding acute pain or pain associated with a concurrent medical condition. One hundred nineteen publications in 28 LMICs were identified for systematic review; the 68 reports that focused on general adult populations (GP), elderly general populations (EGP), or workers (W) were evaluated using mixed-effects regression meta-analysis. RESULTS: Average chronic pain prevalence is reported as a percentage of the population, with 95% confidence interval for each pain type and population (GP, EGP, and W; NA is equal to not available): unspecified chronic pain (34[26–42], 62[41–81], and NA); low back pain (21[15–27], 28[16–42], and 52[26–77]); headache (42[27–58], 30[19–43], and 51[13–88]); chronic daily headache (5[3–7], 5[1–12], and 10[0–33]); chronic migraine (GP 12[6–19]); chronic tension type headache (GP 8[3–15]); musculoskeletal pain (25[19–33], 44[28–62], and 79[60–94]); joint pain (14[11–18], 34[16–54], and NA); chronic pelvic/prostatitis pain (GP 4[0–14]); temporomandibular disorder (35[4–78], 8[0–24], and NA); abdominal pain (EGP 17[6–32]); fibromyalgia (Combined GP, EGP, W 6[5–7]); and widespread pain (7[1–18], 19[8–32], and NA). Chronic low back pain and musculoskeletal pain were 2.50 (1.21–4.10) and 3.11 (2.13–4.37) times more prevalent among W, relative to a GP. Musculoskeletal, joint, and unspecified pain were 1.74 (1.03–2.69), 2.36 (1.09–4.02), and 1.83 (1.13–2.65) times more prevalent among the EGP, relative to a GP. There was significant heterogeneity among studies for all pain types ( I 2 > 90%). CONCLUSIONS: Chronic pain is prevalent in LMICs, and where there was sufficient evidence, generally more prevalent in EGP and W. This meta-analysis reveals the spectrum of chronic pain without clear etiology in LMICs. Steps should be taken to reduce heterogeneity in the assessment of global chronic pain. Possible actions may include standardization of chronic pain definition, widespread adoption of validated questionnaires across cultures, attention to inequitably burdened populations, and inclusion of queries regarding known associations of chronic pain with social and psychological factors that, in combination, increase the global burden of noncommunicable disease and disability. Abstract : Supplemental Digital Content is available in the text.